(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article “Linguistic Features of Retrospection and Prospection” explores the fundamental temporal-cognitive mechanisms through which speakers structure past and future events in discourse. Retrospection and prospection, as complementary categories of temporal orientation, serve not only as grammatical or lexical indicators of time but also as key cognitive frameworks that shape narrative organization, communicative intention, and the speaker’s subjective evaluation of events. In modern linguistics, these phenomena are increasingly analyzed within cognitive, pragmatic, and discourse analytical approaches, emphasizing their role in meaning-making processes. This study examines the linguistic markers that signal retrospection—such as past tense forms, temporal adverbs, evaluative constructions, and narrative flashbacks—and prospection—manifested through future-oriented modal constructions, predictive statements, hypothetical structures, and anticipatory discourse markers. Special attention is given to how these linguistic devices contribute to narrative cohesion, shape semantic coherence, and reflect the speaker’s psychological perspective toward events. Retrospective structures often frame the speaker’s interpretation of past experiences, while prospective structures enable prediction, planning, expectation, and discourse projection. The article also highlights the pragmatic functions of retrospection and prospection in various discourse types, including literary texts, academic writing, conversational exchanges, and media discourse. Retrospective elements are shown to construct background information, provide justification, and enhance emotional resonance, whereas prospective elements play a central role in expressing intentions, formulating assumptions, and guiding listener expectations. By integrating insights from cognitive linguistics, discourse studies, and pragmatics, the research demonstrates that retrospection and prospection are not merely temporal markers but dynamic linguistic strategies that shape how individuals conceptualize time and communicate their worldview. The study concludes that understanding the linguistic features of retrospection and prospection allows for a deeper interpretation of narrative structures and enhances the analysis of temporal semantics in contemporary linguistics. The findings have practical relevance for language teaching, translation studies, text analysis, and intercultural communication, where temporal framing and speaker perspective play an essential role in effective meaning transmission.